Metáforas do Corpo nas Saturae de Aulo Pérsio Flaco - Castro, Mariha Barbosa e (2020)
Aulus Persius Flaccus Satires are usually described as one of the most enigmatic works of Roman literature. Tradition has read, on a regular basis, the complexity of its poems as a strategy to covertly criticize Nero s government. The hypothesis that the